2005
DOI: 10.1227/01.neu.0000170541.23101.81
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prolonged Postprocedural Hypotension after Carotid Artery Stenting

Abstract: Our scoring system, which includes angiographic and ultrasonographic findings, may be a good index for the prediction of prolonged hypotension after carotid stenting and may contribute to the reduction of periprocedural ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 17 publications
1
62
1
Order By: Relevance
“…31,32 The distance between the carotid bifurcation and the maximum stenotic lesion (Յ10 mm) was reported to be an independent risk factor for carotid artery stent placement in 31 patients, as lesions with maximum stenosis Ͼ10 mm from the carotid bifurcation were associated with a low incidence of hypotension. 33 Hyperperfusion syndrome 34 occurred frequently in our patients with body-type lesions, suggesting that the carotid body has a hemodynamic effect on the ipsilateral cerebral circulation.…”
Section: Discussionmentioning
confidence: 71%
“…31,32 The distance between the carotid bifurcation and the maximum stenotic lesion (Յ10 mm) was reported to be an independent risk factor for carotid artery stent placement in 31 patients, as lesions with maximum stenosis Ͼ10 mm from the carotid bifurcation were associated with a low incidence of hypotension. 33 Hyperperfusion syndrome 34 occurred frequently in our patients with body-type lesions, suggesting that the carotid body has a hemodynamic effect on the ipsilateral cerebral circulation.…”
Section: Discussionmentioning
confidence: 71%
“…[1][2][3]12,13,[15][16][17][18] To date, the risk factors that have been found to be independently associated with a higher risk of hypotension and bradycardia during or after CAS are as follows: older age, 14,18 female, 18 previous MI, 13,18 history of CAD, 14 intraprocedural hypotension or bradycardia, 13 stenosis localization (on the carotid bulb or within 10 mm of the carotid bulb), 2,3,16 stenosis length, 3 presence of calcification, 2,16 fibrous plaque, 16 eccentric plaque, 16 high balloon-toartery diameter ratio, 3 and presence of a contralateral stenosis, 3 ; whereas a history of a previous CEA was found to be associated with a lower risk. 2 In the present study, because the baseline values of systolic BP and PR are variable from one patient to another, we preferred to use their relative percentage change rather than their absolute value.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][12][13][14][15][16][17][18] The study end points, as well as the time point and the duration of the vital sign (VS) monitoring, are also highly variable. Absolute blood pressure (BP) and pulse rate (PR) values 2,3,13,14,[16][17][18] or absolute decrease in their initial values 1,3,16 are used in most reports, and a standardized follow-up time for VS monitoring is rarely defined. 3,14,18 This study aimed to assess the predictors of hypotension and bradycardia occurring in the 12 hours after CAS by using the relative decrease of BP and PR as primary end points and the requirement of pressor or anticholinergic drugs as a surrogate end point.…”
mentioning
confidence: 99%
“…9,10 Patients with periprocedural hypertension (Ͼ160 mm Hg), which, in other reports, was included for hemodynamic depression or instability, 3,11 were evaluated separately. Postprocedural transient hypertension was noticed in 21 patients, who had 13 apical lesions and 8 body lesions.…”
Section: Carotid Brmentioning
confidence: 99%
“…2 Hemodynamic depression after CEA and stent placement consists of hypotension related to baroreceptor stimulation and bradycardia or asystole. [8][9][10][11][12][13] Although regarded as a BR, hypertension after CEA or stent placement may have different effects on the immediate outcome after the stent placement procedure by resulting in hyperperfusion. 11,[13][14][15] Our previous study revealed no difference in hemodynamic depression between apical and body lesion locations, probably because patients showing postprocedural hypertension were included.…”
mentioning
confidence: 99%